(untitled) (Revista História: Debates e Tendências, 2018)
For the Italian Partito Nazionale Fascista (Pnf) and the Falange Española (Fe), the political community coincided with the nation, conceived not as an undifferentiated conglomeration of citizens but as a community of believers in a ‘religion of the Fatherland’. The common goal of the Italian and the Spanish fascists, since their appearance on the political scene of their respective countries, was the defence of national values. But the claim to being the only and exclusive representatives of those values denied any effective freedom of dissent, even to those who respected national values but intended them in a different way. This article will analyse how the ideologues of the Pnf and the Fe articulated their respective campaigns against the anti-national enemies in order to legitimise their own parties and pave the way to the effective realization of their own nations: nations that had to be clearly and totally fascist.